2017
DOI: 10.3233/jad-170153
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Metabolic Profile and the Risk of Late-Life Cognitive Decline

Abstract: Abstract. Among metabolic syndrome components, the effects of higher plasma glucose levels on cognitive decline (CD) have been considered in few studies. We evaluated the associations among midlife glycemia, total cholesterol, high-density lipoprotein cholesterol, triglycerides, midlife insulin resistance [homeostasis model assessment for insulin resistance (HOMAindex)], and CD in the older subjects of the population-based MICOL Study (Castellana Grotte, Italy) at baseline (M1) and at follow-ups seven (M2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…Mean homeostasis model assessment for insulin resistance (HOMA) index value was significantly higher in the moderate-severe CD subgroup compared to the normal cognition subgroup at baseline, highlighting the indication to control blood glucose levels, regardless of a diagnosis of diabetes mellitus, as early as midlife for prevention of late-life dementia. [ 8 ] Since some of the complications of diabetes correlate with severe mortality, it is accepted that early detection, diagnosis of diabetes and take action to prevent diabetes development or its complications is of importance. Regular health examination is an important way for early detection of diabetes and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Mean homeostasis model assessment for insulin resistance (HOMA) index value was significantly higher in the moderate-severe CD subgroup compared to the normal cognition subgroup at baseline, highlighting the indication to control blood glucose levels, regardless of a diagnosis of diabetes mellitus, as early as midlife for prevention of late-life dementia. [ 8 ] Since some of the complications of diabetes correlate with severe mortality, it is accepted that early detection, diagnosis of diabetes and take action to prevent diabetes development or its complications is of importance. Regular health examination is an important way for early detection of diabetes and glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In the Chinese and Japanese culture, tea is traditionally consumed without sugar, milk and creamer, while the practice of using additives is common in Western populations. A previous study showed that blood glucose concentration, regardless of a diagnosis of diabetes mellitus, is a risk factor of late life cognitive decline [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Rosanna Tortelli et al examined the cognitive status of Italian population compared with their metabolic status in a study conducted in 1985. They found that those with insulin resistance or diabetes in 1985 had an increased risk of suffering dementia 20 years later [67]. Chronic metabolic alterations have cardiovascular and believed to be cerebrovascular effects.…”
Section: Aging and Dementiamentioning
confidence: 99%